The Comparison between Male and Female Students’ Reading Comprehension - Aisyah Putri Prawira; R. Roswati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The problem of this research was the students’ reading comprehension between male and female student in analytical exposition text such as some of students took a lot of time to catch the idea from the analytical exposition text, and some of students get difficulty to analyze the generic structure and language feature. This research was conducted at eleventh grade of State Senior High School 11 Pekanbaru. This research was a comparative research. The subject of this research was the eleventh grade of State Senior High School 11 Pekanbaru. The researchers took 84 students as the sample of the research. The way in taking the sample was cluster sampling. The instrument of this research was test. It was used to get data about the male and female students’ reading comprehension in analytical exposition text. Whereas, the researchers used independent sample t-test by using SPSS 17.00 version to analyzed the data. Based on the researchers’ findings that t o or t-calculation is lower than t-table on 5% and 1% (1.98 < 3.421 >2.63) with the degree freedom is 82. It means that there is a significant different between male and female students’ reading comprehension in analytical exposition text at eleventh grade of State Senior High School 11 Pekanbaru. This research was done to find out the significant different between male and female students’ reading comprehension in analytical exposition text at eleventh grade of State Senior High School 11 Pekanbaru. Based on the researchers’s findings that there is a significant different between male and female student’s reading comprehension in analytical exposition text.